A guide to measuring phagosomal dynamics - Levin‐Konigsberg, Roni (FEBS J, 2020)
Phagocytosis is an essential mechanism for immunity and homeostasis, performed by a subset of cells known as phagocytes. Upon target engulfment, de novo formation of specialized compartments termed phagosomes takes place. Phagosomes then undergo a series of fusion and fission events as they interact with the endolysosomal system and other organelles, in a dynamic process known as phagosome maturation. Because phagocytes play a key role in tissue patrolling and immune surveillance, phagosome maturation is associated with signaling pathways that link phagocytosis to antigen presentation and the development of adaptive immune responses. In addition, and depending on the nature of the cargo, phagosome integrity may be compromised, triggering additional cellular mechanisms including inflammation and autophagy. Upon completion of maturation, phagosomes enter a recently described phase: phagosome resolution, where catabolites from degraded cargo are metabolized, phagosomes are resorbed, and vesicles of phagosomal origin are recycled. Finally, phagocytes return to homeostasis and become ready for a new round of phagocytosis. Altogether, phagosome maturation and resolution encompass a series of dynamic events and organelle crosstalk that can be measured by biochemical, imaging, photoluminescence, cytometric, and immune‐based assays that will be described in this guide.